Desarrollo de una aplicación web y móvil para la gestión de guías fotográficas digitales de identificación de plagas y enfermedades de los cultivos andinos en la Provincia de Cotopaxi utilizando el Framework Ionic y angular. - Caillagua Yanez, Luis Ramiro (2023)
A web and mobile application was developed using the Ionic and Angular frameworks to automatically design digital guides that contain text and photographs of potato diseases and pests found through field research carried out in the sectors of Cantón Saquisilí, Barrio Canchagua and Miraflores, Latacunga Canton, Aláquez Parish, Los Chillos and Tandaliví neighborhood and in the Salcedo canton Mulalillo and Cusubamba parish belonging to the Cotopaxi province. The digital photographic guides will be managed by students or teachers of the Agronomy Career belonging to the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi Salache extension, which will be consumed by the mobile application.